Characteristics of Ralstonia solanacearum Strains of Potato Wilt Disease from Nepal and Thailand - Dhital, Shambhu P; Thaveechai, Nanda; Shrestha, Sundar K (Nepal Agriculture Research Journal, 2011)
Characterization of strains of Ralstonia solanacearum, the causal agent of potato bacterial wilt disease from Nepal and Thailand was performed based on pathogenicity, biochemical/physiological and serological tests. Fifteen R. solanacearum strains isolated from wilt infected potato plants and tubers grown in Nepal were characterized as race 3, biovar II based on the pathogenicity on different host plants, hypersensitive reaction on tobacco leaf and utilization of some sugars. Results of pathogenicity test show that all strains from Nepal had limited host range. Degree of virulence of all strains varied from high to medium in potato and tomato and medium to low in eggplant. They did not cause wilting in tobacco, pepper and peanut plants. Six strains from Thailand were characterized as biovar II and III. Additionally, comparisons on the physiological, biological and serological characters of seven strains from Nepal and six from Thailand revealed similar characters. Race 3 and biovar II of the pathogen was widely spread over potato growing areas of mid and high hills of Nepal. Both biovars II and III were prevalent in the potato growing areas of Thailand but biovar III was the most dominating one. Key words: Bacterial wilt; Potato; Pseudomonas solanacearum; Ralstonia solanacearum DOI: http://dx.doi.org/10.3126/narj.v4i0.4868 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 42-47 Uploaded date: 9 June, 2011